2015
DOI: 10.1002/lno.10212
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and protist community changes during a phytoplankton bloom

Abstract: The present study aims to characterize the change in the composition and structure of the bacterial and microzooplankton planktonic communities in relation to the phytoplankton community composition during a bloom. High‐throughput amplicon sequencing of regions of the 16S and 18S rRNA gene was undertaken on samples collected during a 20 day (d) mesocosm experiment incorporating two different nutrient addition treatments [Nitrate and Phosphate (NPc) and Nitrate, Phosphate and Silicate (NPSc)] as well as a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…Furthermore, these bacteria lineages cover those groups responsible for both monomer (such as amino acids) and polymer (such as chitin and protein) degradation in the ocean [ 53 ]. Less than 100 bacterial OTUs were assigned in our culture system, which is far less than previous field studies [ 45 , 54 ]. Bacterial community results from laboratory cultures show a lower diversity of bacterial assemblages because long-term maintenance may have eliminated those species that had already been overwhelmed and laboratory studies could avoid invasion of accidental species that are common in field studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, these bacteria lineages cover those groups responsible for both monomer (such as amino acids) and polymer (such as chitin and protein) degradation in the ocean [ 53 ]. Less than 100 bacterial OTUs were assigned in our culture system, which is far less than previous field studies [ 45 , 54 ]. Bacterial community results from laboratory cultures show a lower diversity of bacterial assemblages because long-term maintenance may have eliminated those species that had already been overwhelmed and laboratory studies could avoid invasion of accidental species that are common in field studies.…”
Section: Discussionmentioning
confidence: 98%
“…Bacterial community results from laboratory cultures show a lower diversity of bacterial assemblages because long-term maintenance may have eliminated those species that had already been overwhelmed and laboratory studies could avoid invasion of accidental species that are common in field studies. This is also the reason for which some studies exclude those rare species in their analysis [ 54 ]. The only study addressing the interaction between a Dinophysis bloom and the microbial community revealed that, even during the peak of a Dinophysis acuminata bloom (cell density ~1300 cell mL −1 ), the Dinophysis cells only accounted for 29% of the phytoplankton community [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lehman, Abella, Litt, and Edmondson (2004) in their study concluded that there was a mix of correlations which was more dependent on specific species. Other studies have shown that phytoplankton acted as a competitor for resources, especially nutrients (Pearman, Casas, Merle, Michell, & Irigoien, 2016) as well as secreted algicidal compounds which were negative forces for bacteria growth (Natrah, Bossier, Sorgeloos, Yusoff, & Defoirdt, 2014). Nannochloropsis sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kang’s 23S universal primer set could detect 200-fold changes during the bloom, which means that this primer set was much more sensitive than the 16S primer set in terms of detecting changes in phytoplankton species during various aquatic events, including the bloom, eutrophication, or other ecological transitions. Alternatively, 18S universal primer set can be used to detect changes in eukaryotic algal species ( Bradley, Pinto & Guest, 2016 ; Pearman et al, 2016 ; Stoeck et al, 2010 ; Tragin, Zingone & Vaulot, 2018 ). Recently 18S universal primer successfully amplified the eukaryotic algae with high specificity without bacterial sequences.…”
Section: Discussionmentioning
confidence: 99%